Pola Asuh Keluarga dalam Menumbuhkan Minat Baca Anak sebagai Implementasi Literasi Keluarga - Julianto, Indra Rasyid; Umami, Annisa Sauvika (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
This article examines the parenting styles of parents who have the external task of fostering, leading and managing the care of children. Literacy in children focuses on reading and writing activities from an early age. These activities can be called pre-reading and pre-writing activities. There are subjects in this research, namely two families who have children in preschool age, namely 0-6 years in Ledeng Village, Cidadap District, Bandung City. Data collection in research uses interview, survey and documentation techniques. Then the data analysis techniques in this research are data collection, data reduction, data presentation, and conclusions. Based on research results, children's reading success and literacy culture are influenced by the family environment that shapes them. The more positive stimulation and influence given to children, such as the introduction of vocabulary and support for reading, the faster children can understand the writing they read and are able to encourage the success of a literacy culture in the family. The results were found in two different family samples and based on these results it was found that the more positive stimulation provided, such as the introduction of vocabulary and support for reading, the faster children can understand the writing they read and are able to encourage the success of a literacy culture in the family. Keywords:Family literacy;Implementation;cChiledres's;Family Parenting